EWOM towards Homestays Lodging: Extending the Information System Success Model - Rizal Hamid; Soffri Yussof; Hanudin Amin; Ku Chen-Jung (2018)
Purpose: Drawing from DeLone and McLean’s Theory of Information System Success, this study aims to develop a theoretical model of electronic word of mouth (eWOM) for the homestay lodging. Design/methodology/approach: The study examines the relationship between information quality, system quality and electronic service quality towards user’s satisfaction and eWOM intentions. Data were collected from homestay lodgers in Malaysia. Findings: Results indicate that the effects of information quality and e-service quality on satisfaction are of significance, in turn affects eWOM intention. System quality, however, is not a driver of satisfaction. Research limitations/implications: This study contains three limitations that provide direction for future studies. The details are provided. Practical implications: The results provide a direction to the service providers at improving their services for customers’ satisfaction and loyalty. Originality/value: The study offers fresh new insights on eWOM intentions from a homestay lodging perspective in Malaysia.